Low-Protein Diet Supplemented with Keto Acids Is Associated with Suppression of Small-Solute Peritoneal Transport Rate in Peritoneal Dialysis Patients. (27th June 2011) - Jiang, Na; Qian, Jiaqi; Lin, Aiwu; Fang, Wei; Zhang, Weiming; Cao, Liou; Wang, Qin; Ni, Zhaohui; Yao, Qiang
Abstract : Objective. We investigate whether low-protein diet would show benefits in suppressing peritoneal transport rate in peritoneal dialysis (PD) patients. Methods. This is a supplemented analysis of our previously published trial, which randomized 60 PD patients to receive low- (LP: dietary protein intake of 0.6–0.8 g/kg/d), keto-acid-supplemented low- (sLP: 0.6–0.8 g/kg/d with 0.12 g/kg/d of keto acids), or high- (HP: 1.0–1.2 g/kg/d) protein diet and lasted for one year. In this study, the variations of peritoneal transport rate were assessed. Results. While baseline D/Pcr (dialysate-to-plasma concentration ratio for creatinine at 4 hour) and D/D0glu (dialysate glucose at 4 hour to baseline dialysate glucose concentration ratio) were similar, D/Pcr in group sLP was lower, and D/D0glu was higher than those in the other two groups (P < 0.05 ) at 12th month. D/D0glu increased (P < 0.05 ), and D/Pcr tended to decrease, (P = 0.071) in group sLP. Conclusions . Low-protein diet with keto acids may benefit PD patients by maintaining peritoneum at a lower transport rate.